Active Galactic Nuclei and Galaxy Interactions - Alonso, M. Sol (2007)
We perform a statistical analysis of AGN host characteristics and nuclear activity for AGNs in pairs and without companions. Our study concerns a sample of AGNs derived from the SDSS-DR4 data by Kauffmann et al (2003) and pair galaxies obtained from the same data set by Alonso et al. (2006). An eye-ball classification of images of 1607 close pairs (rp < 25 kpc h −1 , ∆V < 350 km s −1 ) according to the evidence of interaction through distorted morphologies and tidal features provides us with a more confident assessment of galaxy interactions from this sample. We notice that, at a given luminosity or stellar mass content, the fraction of AGNs is larger for pair galaxies exhibiting evidence for strong interaction and tidal features which also show sings of strong star formation activity. Nevertheless, this process accounts only for a ∼ 10% increase of the fraction of AGNs. As in previous works, we find AGN hosts to be redder and with a larger concentration morphological index than non-AGN galaxies. This effect does not depend whether AGN hosts are in pairs or in isolation. The OIII luminosity of AGNs with strong interaction features is found to be significantly larger than that of other AGNs, either in pairs or in isolation. Estimations of the accretion rate, L[OIII]/MBH , show that AGNs in merging pairs are actively feeding their black holes, regardless of their stellar masses. We also find that the luminosity of the companion galaxy seems to be a key parameter in the determination of the black hole activity. At a given host luminosity, both the OIII luminosity and the L[OIII]/MBH are significantly larger in AGNs with a bright companion (Mr < −20) than otherwise.